Comprehensive analysis provides insights into Ziyang xiangcheng (Citrus junos Sieb.) tolerance of alkalinity stress - Chenyu Xu; Junying Cao; Mei Su; Xianshuo Yan; Hualin Yi; Haijian Yang; Juxun Wu (Fruit Research)
Alkaline soil is one of the major problems affecting the development of the citrus industry. Ziyang xiangcheng (Citrus junos Sieb. ex Tanaka) (Cj) is an alkalinity stress-tolerant citrus rootstock. In this study, two citrus rootstocks (Cj and Poncirus trifoliata (L.) Raf.) (Pt)) and one navel orange scion ('Lane Late' navel orange (Citrus sinensis (L.) Osb.) (LL)) were used. The root, stem and leaf tissues of grafted materials Cj + LL and Pt + LL grown in calcareous soil were used to identify genes and pathways that are responsive to alkalinity stress using comparative transcriptomics. Seedlings of Cj and Pt cultured in nutrient solutions at three pH grades were used to perform a supplemental experiment. A comprehensive analysis of the RNA-seq data, physiology, biochemistry, agronomic traits and mineral elements of the Cj + LL, Pt + LL, Cj and Pt materials revealed several candidate pathways and genes that were highly regulated under alkalinity stress. The data suggest that the jasmonate pathway may play crucial roles in tolerance to alkalinity stress in Cj by interacting with other plant hormones, lignin biosynthesis and the ROS scavenging system. These results provide new clues for future investigations of the mechanisms underlying the tolerance of citrus to alkalinity stress.